Rhodium-catalyzed tunable oxidative cyclization toward the selective synthesis of α-pyrones and furans. Issue 8 (14th December 2015) - Wu, Jiaping; Wang, Dongxu; Wan, Yanjun; Ma, Cheng
Abstract : The Rh III -catalyzed tunable oxidative cyclization of readily available N -tosylacrylamides and diazo compounds toward the selective synthesis of fully substituted furans and α-pyrones is presented. Abstract : The rhodium(iii )-catalyzed tunable oxidative cyclization of readily available N -tosylacrylamides and diazo compounds is presented, which offers a novel method for the selective construction of fully substituted α-pyrones and furans in a regiospecific manner by employing the acylsulfonamide group as a versatile in situ removable directing group.